FRI0341 Temporomandibular joints (TMJ) involvement in juvenile idiopathic arthritis (JIA): Longitudinal evaluation after orthopaedic treatment. (23rd January 2014) - Falcini, F.; Melchiorre, D.; Cappelli, S.; Carnesecchi, G.; Biondi, K.; Bosco, M.; Matucci Cerinic, M.
Abstract : Background: TMJ involvement has been largely observed in all subsets of patients with JIA. The reported prevalence of detectable X-ray changes varies from 30% to 63%. From 50 to 80% of JIA children, may have TMJ arthritis by MRI and by sonographic exam (SE) (effusions, synovial enhancement, condylar flattening and/or erosions, thickness of masseter muscle) before evidence of X-ray damage. TMJs injections with steroids or/and anti-TNF alpha blockers have been used at the first signs of inflammation. When joint damage is evident orthopaedic treatment (brace) may be helpful in preventing its further evolution. Objectives: To evaluate the efficacy and safety of orthopaedic treatment in a cohort of JIA adolescents/young adults with TMJ arthritis. Methods: Our study population included 90 JIA consecutive pts (66 F, 24 M, mean age 14, 5.±4, 4 yrs.), mean age at disease onset 6, 9±5 yrs., mean disease duration at first orthodontic evaluation 7, 7±5, 2 yrs., all treated at Transition clinic of Rheumatology Department between January 2010 and December 2011. Out of 90 pts, 45 had oligoarticular, 32 polyarticular, 4 systemic, 9 enthesitis-related onset. The diagnosis of TMJ disease was performed on the presence of at least one Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) diagnosis. The anamnestic and functional data were collected in a medical record used by orthodontists of University of Pavia, Italy. 50.1% of the pts complained of recurrent pain localized in the temporomandibular area, crepitation, and jaw stiffness or fatigue. All TMJs were examined by panoramic X-ray, teleradiography with latero-lateral and antero-posterior view, and by SE with Esaote MyLAB 70 (Genoa Italy linear probe 8-13 MHz). At first orthodontic evaluation 80/90 pts showed dento-skeletal malocclusions leading to a Class II caused by skeletal retrognathia, post-mandibular rotation, lower height of the mandibular body and ramus that can determine asymmetry in the frontal and/or in the sagittal plane. Fifty five out of 90 pts (61.1%) received orthopaedic treatment with an activator to help mandibular growth, followed by the use of a bite. Twenty five/90 pts (28%) have worn a bite without previous orthopaedic therapy, 10 pts (11.1%) refused treatment. Results: After two years from the first orthodontic evaluation 58 out 80 pts who underwent either orthopaedic therapy plus bite or bite alone (72.5%) showed an improvement in occlusion, masticatory function and cranio-facial morphology.In 75/80 pts (94%) the thickness of masseter muscle, detected by SE after treatment, was similar on left and right side (mean value 7.6 mm) at rest and after contraction (p<0.001). In all JIA pts SE showed bone remodelling of the condyle head; in 30/45 pts with oligoarthritis (66.7%) monolateral erosions were present. Conclusions: Our data confirm that in JIA patients, TMJs orthopaedic treatment may modify the severe and often intractable damage responsible of severe micrognathia, aberrations in mandibulofacial development, and facial asymmetry. TMJ orthopaedic treatment is recommended when local steroid/anti TNF alpha blockers injections are not indicated to block the bone damage. Disclosure of Interest: None Declared